2016
DOI: 10.1186/s13104-016-2182-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of CD4 count over time among HIV patients initiated ART in Felege Hiwot Referral Hospital, northwest Ethiopia: multilevel analysis

Abstract: BackgroundThe response of HIV patients to antiretroviral therapy could be measured by its strong predictor, the CD4+ T cell (CD4) count for the initiation of antiretroviral therapy and proper management of disease progress. However, in addition to HIV, there are other factors which can influence the CD4 cell count. Patient’s socio-economic, demographic, and behavioral variables, accessibility, duration of treatment etc., can be used to predict CD4 count.MethodsA retrospective cohort study was conducted to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
38
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 35 publications
(50 reference statements)
14
38
2
Order By: Relevance
“…The progression change about √ (CD4 cell) count on patients for those bedridden functional status patients was less than those working functional status when controlling other independent variables. This study agreed with the findings of [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The progression change about √ (CD4 cell) count on patients for those bedridden functional status patients was less than those working functional status when controlling other independent variables. This study agreed with the findings of [19].…”
Section: Discussionsupporting
confidence: 93%
“…In ART follow-up, CD4 cell is measured repetitively over time and this rise of CD4 cell change at every visiting time inspires the patient to be a good adherent to their regimen [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Another cohort study in ARV Thai adult patients with advanced HIV infection showed that NVP-and EFV-based HAART regimens were equally effective in terms of virological and immunological responses (Lapphra et al, 2008). The positive association between younger age groups and better immune recovery demonstrated comparably among the two groups in this study which is in congruence with other previous pediatric and adult reports (de Castilla et al, 2008;Reda et al, 2013;Gezie, 2016;Asfaw et al, 2015;Eshun-Wilson et al, 2012). This might be justified by high reserve of lymphocytes cell and early initiation of ART among younger age groups.…”
Section: Discussionsupporting
confidence: 89%
“…The high proportion of patients (83%) in this condition may partly explain this finding. Gezie et al [24] found Age as a predictor of CD4 counts over time in Ethiopia. Younger age was positively correlated to CD4 count increase during the course of treatment.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%